PENUNDAAN PENJEPITAN TALI PUSAT TERHADAP KADAR BILIRUBIN BAYI BARU LAHIR - Astuti, Dyah Puji; Indriyastuti, Hastin Ika; Novyriana, Eka (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Delayed cord clamping can have an effect on the hematological value of the newborn. The advantages of cord clamping delays include preventing anemia, increasing hematocrit levels, reducing postpartum incidence, optimizing oxygen transfusion to the baby, improving maternal and infant closeness and promoting infant brain growth. The disadvantage of cord clamping delays is the occurrence of hyperbilirubin and policitemia in newborns. The purpose of this study was to identify the levels of bilirubin newborns. The research method used True Experimental Design in 3 (three) treatment groups; treatment of umbilical delayed cord clamping (DCC) for 2 minutes after birth; delay cord clamping (DCC) for 3-7 minutes /until stop pulsating; and delayed cord clamping (DCC) up to 2 hours. The results showed that the highest average bilirubin levels were found in the 2 minute DCC treatment group with mean value (4.04)